Mating disruption of pea moth (Cydia nigricana) in organic peas (Pisum sativum). Issue 3 (7th January 2014) - Saucke, H.; Balasus, A.; Finckh, M.R.; Formowitz, B.; Schmidt, R.; Kratt, A.
Abstract We appraised mating disruption (MD) to control pea moth, Cydia nigricana (Fabricius) (Lepidoptera: Tortricidae), by assessing male attraction to monitor traps, larval pod infestation, and larval age structure in pheromone‐treated and untreated grain pea fields [Pisum sativum L. (Fabaceae)], over a 5‐year period. Cellulose pheromone dispensers were manually attached to the top shoots of pea plants and released 540 mg ha−1 day−1 synthetic pheromone E8, E10‐dodecadien‐1‐yl acetate in a first test series (2000–2001) and ca. 4 200 mg pheromone ha−1 day−1 in a second series (2004–2006). The dispensers had a half‐life of about 30 days. Although male attraction to pheromone monitoring traps was largely suppressed at the edges and within MD fields in both test series, MD treatments did not reduce pod infestation in the open field in 2000 and 2001. In the 2004–2006 series, larval damage reduction was achieved in the majority of the trials but overall MD efficacy in the open field was only 61% and not significant. In contrast, in field cages placed within the experimental sites and supplied with unmated pea moths, MD control was consistently high and significant. There were no obvious differences in the larval age distribution in all MD and control treatments, suggesting that infestations started and developed further similarly. As a univoltine species, C. nigricana larvae stay in the soil of pea fields for hibernation and pupate. The following year, emerging adults disperse and fly to the closest pea crop. Combined emergence site and pea crop treatments were conducted over 2 years to include this early migration phase of C. nigricana adults. However, the emergence site treatments did not enhance MD‐control efficacy. We conclude that mating activity was only prevented in cage tests, whereas substantial mating occurred during the transit phase outside the pheromone‐treated fields either within non‐crop vegetation and/or at the edges of pheromone‐treated pea fields orientated upwind. Thus, resulting gravid female entry can be regarded as the major constraint to reliable MD control.